(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2020)
The Upper Cretaceous carbonate platform deposits of Ostuni have been studied from a stratigraphical, palaeontological and palaeoecological point of view. ln the sequence studied two parts can be distinguished: the Iower one consists of stratified biomicritic limestones with clusters of rudists, other pelecypods and microfauna, represented by ostracods algae and benthonic foraminifers; the upper one consists of a sequence of coral—rudist buildups with banks of calcarenites and calcirudites characterized by trace fossil assemblages, gastropods, rudists, other pelecypods and benthonic and planktonic foraminifers.